2019
DOI: 10.1016/j.mex.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effects of vitamin A against gamma radiation in mouse bone marrow cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
6
0
1
Order By: Relevance
“…With the understanding that free radicals perpetuate a significant amount of the damage caused by IR, vitamins with antioxidant potential (A, C, and E and its derivates) have been assayed as radioprotectors. Vitamin A and carotenes have antioxidant activity and capacity to enhance DNA repair, and in vivo reduced mortality and morbidity in mice exposed to partial or TBI [ 165 ]. Carotenoids such as crocin and crocetin (isolated from saffron) have antioxidant, anti-inflammatory and antiapoptotic effects [ 166 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…With the understanding that free radicals perpetuate a significant amount of the damage caused by IR, vitamins with antioxidant potential (A, C, and E and its derivates) have been assayed as radioprotectors. Vitamin A and carotenes have antioxidant activity and capacity to enhance DNA repair, and in vivo reduced mortality and morbidity in mice exposed to partial or TBI [ 165 ]. Carotenoids such as crocin and crocetin (isolated from saffron) have antioxidant, anti-inflammatory and antiapoptotic effects [ 166 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Charles River 3 , Taconic 4 , LabDiet 5 ) routinely make the composition of their diets publicly available; however, it is incumbent on researchers to ensure that the content of the feed will not impact the radiation exposure study. For example, many diets include known radiation injury protectants/mitigators, such as soy products (Ohara et al 2001;Hillman et al 2011;Abernathy et al 2017;Landauer et al 2019), vitamin A (Seifter et al 1988;Harapanhalli et al 1994;Roche et al 2015;Changizi et al 2019), vitamin C (Narra et al 1994;Konopacka et al 1998 2003; Erol et al 2004;Singh et al 2013). In addition, certain estrogens (Wang et al 2005;Fucic and Gamulin 2011), which have been shown to influence the degree of damage from radiation exposure, may also be found in rodent chow.…”
Section: Dietmentioning
confidence: 99%
“…Charles River 3 , Taconic 4 , LabDiet 5 ) routinely make the composition of their diets publicly available; however, it is incumbent on researchers to ensure that the content of the feed will not impact the radiation exposure study. For example, many diets include known radiation injury protectants/mitigators, such as soy products ( Ohara et al 2001 ; Hillman et al 2011 ; Abernathy et al 2017 ; Landauer et al 2019 ), vitamin A ( Seifter et al 1988 ; Harapanhalli et al 1994 ; Roche et al 2015 ; Changizi et al 2019 ), vitamin C ( Narra et al 1994 ; Konopacka et al 1998 ; Kanter and Akpolat 2008 ; Satyamitra et al 2011 ; Mortazavi et al 2015 ; Roche et al 2015 ; Zangeneh et al 2015 ; Rostami et al 2016 ; Alexander et al 2018 ; Jafari et al 2018 ), vitamin D ( Langberg et al 2009 ; Gavrilov et al 2010 ; Marampon et al 2016 ) and vitamin E ( Ross et al 1983 ; Shaheen and Hassan 1991 ; Empey et al 1992 ; Nair et al 2003 ; Satyamitra et al 2003 ; Erol et al 2004 ; Singh et al 2013 ). In addition, certain estrogens ( Wang et al 2005 ; Fucic and Gamulin 2011 ), which have been shown to influence the degree of damage from radiation exposure, may also be found in rodent chow.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…El ensayo en roedores está incluido en la batería de estudios toxicológicos exigidos por la OECD. Es fácilmente reproducible, para ello se lava el fémur con suero fetal bovino, la médula se centrífuga a 800-1,000rpm/10 min; se elimina el sobrenadante y con el botón se realiza el frotis (32)(33)(34).…”
Section: Modelos Más Utilizados En La Prueba De Micronúcleosunclassified